Design of a comprehensive performance evaluation model for Tebessa Phosphate Mines Company using the "BSC Designer" software - amrouche, BASSEM (Journal of Research in Finance and Accounting, 2024)
The study aimed to highlight the effective role played by the balanced scorecard in evaluating the performance of the Tebessa Phosphate Mines Company, given the latter's material and human resources. Accordingly, it concluded a set of results, the most prominent of which is that the company under study does not use the balanced scorecard as a tool for formulating and implementing its strategy; that is, it only uses traditional evaluation tools of a financial nature to measure and evaluate financial performance in the short term, in addition to the fact that by using the scorecard designed using the "BSC Designer" software for the year 2021, the three performance indicators (economic, social and environmental) were obtained, through which the company's performance was evaluated for the period studied, and the disclosure process in the company was improved to become comprehensive disclosure in its three dimensions.